Imparting education in human values to primary education students and testing it by implementing a moral maturity scale - (:unkn) unknown (SLOVAK ACAD SCIENCES INST EXPERIMENTAL PSYCHOLOGY, 2003)
The general objective of this study is to expose fourth and fifth grade primary education students to the Educational Human Values (EHV) Program, and to test its effectiveness by implementing a Moral Maturity Scale. The EHV Program was developed by June Auton in England and consisted of five core values called Truth, Love, Peace, Right Conduct, and Non-Violence, and forty-four sub-values. This study is a quasi-experimental one. A model involving a pre-test-post-test control group has been implemented in the study. The target group of our study consisted of fourth and fifth grade primary education orphan students. The result has verified that the EHV Program would improve the moral maturity levels of the students who participated.
Keywords: education human values; Moral Maturity Scale; primary education student; orphanage children; value education